Odpowiedzi

2010-03-18T13:27:03+01:00
A) 3x² - 5x + 2 + 2x - 4 + x²=4x²-3x-2
b) - 4x² - 3 + 2x - x² - 4 - 5=-5x²-12+2x
c) x² - 4x² + 5x - 1 - 3x³ - 4x² - 3x + 5=-10x²+2x+4
e) 9x²-3x+1-6x²-5x-3-6+2x-x²=2x²-6x-8
f) 4-2x-3x²-5x²+2x-3-5+x+4x² =-4+x+4x²


wydaje mi się że jest dobrze, ale gdyby się coś nie zgadzało to napisz na prw to chętnie poprawie:):)
3 5 3
2010-03-18T13:28:50+01:00
A) 3x² - 5x + 2 + 2x - 4 + x²=4x²-3x-2
b) - 4x² - 3 + 2x - x² - 4 - 5=-5x²+2x-12
c) x² - 4x² + 5x - 1 - 3x³ - 4x² - 3x + 5=4-2x-13x²
e) 9x²-3x+1-6x²-5x-3-6+2x-x²=2x²-6x-8
f) 4-2x-3x²-5x²+2x-3-5+x+4x² =-4+x+4x²


1 2 1
Najlepsza Odpowiedź!
2010-03-18T13:29:32+01:00
A)3x² - 5x + 2 + 2x - 4 + x²= 4x² - 3x - 2
b) - 4x² - 3 + 2x - x² - 4 - 5= -5x²-12+2x
c) x² - 4x² + 5x - 1 - 3x³ - 4x² - 3x + 5=-3x³-9x²+2x+4
e) 9x²-3x+1-6x²-5x-3-6+2x-x²=2x²-6x-8
f) 4-2x-3x²-5x²+2x-3-5+x+4x²=-4x²+x-12